Value stability in local real estate markets - Kauko, Tom (International Journal of Strategic Property Management, 2010)
Whenever real estate investments are considered in a more sustainable development framework, the issue is about finding the appropriate criteria of physical, social and economic sustainability. While this topic has business and social policy relevance, academic work on defining the relevant indicators is yet speculative, due to a shortage of standard definitions and relevant data. The general concept of economic sustainability of the property market comprises a variety of more particular measures. In order to design a valid methodology for assessment purposes, in this study a property value stability trend is determined for specific residential areas. This indicator is composed of property sales prices and the quality level of the existing stock in a given area. The findings from a selected demonstration of the development of price‐to‐quality ratios in an urban context have implications for further research as well as for practice.First Published Online: 09 Jun 2011